Real estate information retrieval mobile application system using Quick Response (QR) code / Siti Aishah Ahmad Pisal - Ahmad Pisal, Siti Aishah (2019)
This project presents a mobile application development to retrieve real-time information on real estate property. Real estate market is one of the highly critical process as it involves the human right of property. It consumes a high rate of money profit or loss, including time taken for each process to be done properly. However, in the real estate market, issues such as poor rate of time responding and cases of misleading information may occur due to the difficulty of gaining the real-time data. Hence, this thesis represents a solution that combines the Quick Response (QR) code technology integrated in the mobile application to create a platform that give a good feature of time management and convenience of receiving data for user. The real estate data is taken from the residential area of the market only. Data from several cities in Selangor is used in this project development. The project incorporates Rapid Application Development methodology for the development guidance. The result from this project, which is the application, can be used by any responsible associations as its IT services for marketing and advertisement. The application can be further upgrade to facilitate the real estate industry market.